Development of Augmented Reality Integrated Handouts for Strengthening Independence Character of Junior High School - Nur Alfiyani; Muhammad Syawaludin; Anik Widiastuti (Jurnal Paedagogy)
This study aims to develop Augmented Reality integrated handouts to strengthen the independent character of junior high school students on the material of the relics of Hindu-Buddhist kingdoms in Indonesia. The research used the Research and Development method with the 4D development model (Define, Design, Develop, Disseminate) carried out at SMPN 1 and SMPN 2 Mojowarno, Jombang Regency. The research instruments included material and media expert validation sheets, student response questionnaires for practicality testing, observation sheets and independent character questionnaires to measure product effectiveness. Data were analyzed using quantitative descriptive techniques for validity and practicality with score interpretation criteria, while the effectiveness of strengthening independent character was analyzed using the N-gain test comparing the results of initial and final measurements in the experimental class. The validation results by material experts, media experts, and practitioners showed that the product validity level reached 94.5% which was included in the very valid category. The practicality test obtained a score of 97% in the initial test and 98% in the large-scale implementation of 60 students, both in the very practical category. Measurement of independent character showed a significant increase in both experimental classes with N-gain values reaching 0.92 and 0.90 which were categorized as very independent. This study proves that the Augmented Reality integrated handout effectively strengthens students' independent character while improving understanding of the material of the relics of Hindu-Buddhist kingdoms. This learning media offers an innovative solution that is aligned with the objectives of the Merdeka Curriculum and the Pancasila Student Profile, especially in fostering student independence through the use of digital technology.